Purification of Phenolic Compounds from Camellia polyodonta Flower: Composition Analysis, Antioxidant Property, and Hypolipidemic Activity In Vitro and In Vivo - Zhuoya Xiang; Li Liu; Zhou Xu; Qingbo Kong; Heng Liang; Shiling Feng; Tao Chen; Lijun Zhou; Hongyu Yang; Chunbang Ding (MDPI AG, 2024)
Camellia polyodonta flowers are rich sources of phenolics and less attention has been paid to their potential biological activity. This study aims to explore the crude extracts and resulting purified fractions (CPFP-I, II, III, and IV) through compositional analysis and antioxidant and hypolipidemic activities in vitro and in vivo. Among four fractions, CPFP-II contained the highest total phenolic content and flavonoid content, while CPFP-III exhibited the greatest total proanthocyanidin content. Among the 14 phenolic compounds, CPFP-II displayed the highest content of procyanidin B2, B4, and C1, whereas CPFP-III contained the highest amount of 1,2,3,6-tetragalloylglucose. The DPPH, ABTS, and FRAP assessments demonstrated a consistent trend: CPFP-II > CPFP-III > CPFP-I > CPFP-IV. In vivo experiments showed that that all four fractions significantly reduced lipid levels in hyperlipidemic C. elegans (p < 0.05), with CPFP-II exhibiting the most potent effect. Furthermore, CPFP-II effectively bound to bile acids and inhibited the enzymatic activity of pancreatic lipase in vitro. Consequently, CPFP-II should be prioritized as a promising fraction for further exploration and should provide substantial support for the feasibility of the C. polyodonta flower as a natural alternative.